Propuesta de tratamiento aguas duras, para el sistema de regadío de la comunidad La Primavera - Aguinda Paneso, Christian Jonatan (2024)
La Primavera rural community, located in Chimborazo province, faces serious issues with its irrigation systems due to high water hardness, which reaches concentrations of 221.67 mg/L of CaCO3, primarily caused by the presence of calcium and magnesium ions. This hardness leads to the buildup of minerals and the formation of deposits in pipes, sprinklers, and valves, resulting in frequent blockages, costly equipment replacements, and a reduction in agricultural production efficiency. The objective of this study was to design a treatment system to reduce the hardness of irrigation water, using oxidic lithological material (OLM) from two sources: Santa Clara in Pastaza province and Santa Teresa in Chimborazo. Infrastructure problems were diagnosed, the water was characterized, and a treatment system was designed based on the adsorption of hardness by OLM. The OLM samples were used both in their natural state and activated at different pH levels (2.5 and 11.5), and mixed (mixed bed). Various particle size fractions were evaluated: for Santa Clara, sizes of (75-150 and <75) µm were used, while for Santa Teresa, sizes of (250-150 and 150-75) µm were used, all cut to lengths of 2 to 3 mm. The results showed that the beds activated with NaOH pH (11.5) were the most effective, achieving hardness reduction efficiencies of 71.21% with the Santa Clara OLM and 64.47% with the Santa Teresa OLM, without reaching saturation. The mixed beds also performed well, with Santa Clara OLM being more efficient in retaining anions (chlorides and sulfates), while Santa Teresa excelled in hardness removal. In conclusion, the proposed treatment system offers a viable, economical, and easily implementable solution to improve irrigation water quality in La Primavera. Additionally, it contributes to the longevity of irrigation equipment and supports the agricultural development of the community.